1.2 An Enhanced, Midwifery-Led Ultrasound Service to Monitor Fetal Growth. (26th April 2013) - Tonks, AM; Williamson, A; Williams, A; Gardosi, JO
Abstract : Objective: Antenatal detection of intrauterine growth restriction (IUGR) is a key objective of maternity care. In 2009, 4 in 5 babies in Birmingham born with an SGA birthweight were not recognised as such antenatally, and most high-risk mothers were afforded only one third trimester scan. We set out to improve detection through an enhanced ultrasound screening service for higher risk mothers. Methods: The Community Growth Scanning service (CoGS, www.pi.nhs.uk/cogs ) was established in clinics staffed by midwives trained in 3rd trimester ultrasound. Standardised protocols were agreed with all clinicians, for women requiring scans following abnormal fundal height measurement, or for serial scanning because of increased risk of IUGR. The new service started in Summer 2010 and evaluation included all women who attended and delivered by the end of Dec 2011. Results: 2, 583 women were referred during the study period. The majority (57.1%) were for serial scans and constituted 79.7% of scans undertaken. High-risk mothers were more likely to receive serial scans (mode: 4 scans, 68.3% having 3+), compared to the 2009 baseline (mode: 1 scan; 73% had less than 2). Compared to a background SGA rate of 13.1%, the prevalence in mothers referred for serial ultrasound was 26.2%, with an antenatal detection rate of 47.7% (CI 42.7–52.7%). There were two perinatal deaths of normally formed IUGR babies within this cohort (0.8/1, 000 births, CI 0.0–1.8). Conclusion: Enhanced provision of ultrasound resources to mothers at increased risk results in significant improvements in antenatal detection of IUGR.